Jeux de plateau pour l'agriculture et le paysage Penser, concevoir, animer, évaluer, diffuser - Dernat, Sylvain; MICHELIN, Yves; Blache , Nolwenn (éditions Quae, 2023)
In France and around the world, there's a growing trend towards board games for agriculture and landscaping. Most of the time, this craze is the result of isolated initiatives, successful or not, based on trial and error. Their design can pose a number of problems for novices. This guide proposes to capitalize on this experience to support the design, animation and evaluation of new games in the fields of agriculture and landscape management. The social environment is at the heart of the guide, as the driving force behind the game and the learning, attitudinal changes and actions it generates. The authors propose a highly operational method for designing a game based on an agricultural or landscape issue, ranging from theoretical concepts to the evaluation of the object created. Each chapter includes a detailed case study to help you understand the design process. The authors' decades of experience have gone into the formalization of this methodology, so that this guide can be used in the field by as many novice designers as possible.